STUDENTS’ PERCEPTION TOWARD ENGLISH TEACHERS’ ACADEMIC PERFORMANCE IN THE CLASROOM AT SMP MUHAMMADIYAH AL-AMIN SORONG - Muhaiminah Akib; Abdurrahman Abdurrahman; Mirna Hamid (Universitas Muhammadiyah Sorong, 2016)
The object of this research is describing the students’ perception and to investigate how the students their perception about their teacher in learning process among second grade students of SMP Muhammadiyah Al-Amin Sorong. The method of this research was descriptive quantitative, the collect data is analyzed by using Statistical Package for the Social Science (SPSS) version 17. The survey study was conducted to gather data from respondents. There were 31 students as respondents in this study. The instrument is questionnaire. The students’ perception about their teacher academic performance was in high level category. The students have 2 positive perceptions and one negative perception. Positive perception is in teacher knowledge of subject matter and teacher attitude to work. While negative perception is in the teacher’s skill of teaching the subject matter. Generally, the result of the data analysis and testing hypothesis shows that most of the students gave perception toward their teachers’ performance in teaching and learning process.